Evaluasi Kebijakan Tata Kelola Satuan Perlindungan Masyarakat di Indonesia - Kurhayadi, Kurhayadi; Hadi Kushendar, Deden; Surtiani, Ani (Jurnal Inspirasi, 2021)
This research uses a qualitative approach with a case study design. The data collection technique was carried out by in-depth interviews with 12 informants who were selected using a consideration sampling technique, Focus Group Discussion (FGD) and supported by various documents, especially policies related to the governance of the National Limnas in Indonesia and the City of Bandung. The results of the study indicate that the governance of the community protection unit has not been carried out effectively because the basic policy, namely the Mayor’s Regulation (Perwal) of the City of Bandung cannot be used as a clear reference. The policy does not yet contain a comprehensive governance system, resulting in the unclear mechanism of coordination, collaboration in recruitment, training, implementation, provision of operational funds, and reporting on the organization of Linmas. The results of the study recommend the need for a review of the Mayor of Bandung Regulation Number 1556 of 2018 concerning the Implementation of Community Protection and the Selection Team for Members of the Community Protection Unit and Civil Service Police Assistance Personnel. The need to establish performance indicators for the performance of members of the Community Protection Unit to be able to measure the level of effectiveness and efficiency of the implementation of the Community Protection Unit in the City of Bandung, it is also necessary to place a Satlinmas mechanism under the coordination of the Civil Service Police Unit and those in the District and Kelurahan. ABSTRAK Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Teknik pengumpulan data dilakukan dengan wawancara mendalam kepada 12 orang informan yang dipilih menggunakan teknik sampling pertimbangan, Focus Group Discussion (FGD) dan didukung berbagai dokumen terutama kebijakan terkait tata kelola Limnas di Indonesia dan Kota Bandung. Hasil penelitian menunjukkan tata kelola satuan perlindungan masyarakat belum dilakukan secara efektif dikarenakan dasar kebijakannya, yaitu Peraturan Walikota (Perwal) Kota Bandung belum dapat dijadikan acuan yang jelas. Kebijakan tersebut belum memuat sistem tata kelola yang menyeluruh, sehingga berdampak pada ketidakjelasan mekanisme koordinasi, kolaborasi dalam rekrutmen, pelatihan, pelaksanaan, pemberian dana operasional, dan pelaporan penyelenggaraan Linmas.Hasil penilitian merekomendasikan perlunya dilakukan kajian ulang terhadap Peraturan Walikota Kota Bandung Nomor 1556 Tahun 2018 tentang Penyelenggaraan Perlindungan Masyarakat dan Tim Seleksi Anggota Satuan Perlindungan Masyarakat dan Tenaga Bantuan Polisi Pamong Praja. Perlunya menetapkan indikator capaian kinerja anggota Satuan Perlindungan Masyarakat untuk dapat mengukur tingkat efektivitas dan efisiensi penyelenggaraan Satuan Perlindungan Masyarakat di Kota Bandung, juga diperlukan mekanisme penempatan Satlinmas yang berada di bawah koordinasi Satuan Polisi Pamong Praja dan yang berada di Kecamatan dan Kelurahan.